Low Oxygen Tension Inhibits Senescence in Bone Marrow Mesenchymal Stem Cells (BMSCs) - Candra Bumi (Journal of Agromedicine and Medical Sciences, 2022)
Background: Stem cells have been used in regenerative medicine but are so few in the body that they require cell culture. Stem cell culture was performed under normal oxygen tension and passage was carried out until the number of cells was sufficient for therapy. Stem cell cultures under normal oxygen tension do not match the stem cell microenvironment, which can lead to premature senescence. This study aims to determine the association of low oxygen tension with premature senescence of mesenchymal stem cells (MSCs) through inhibition of p21 expression by HIF-1a. Methode: The research method used rabbit bone marrow in New Zealand as a source of MSCs. The results of isolation of MSCs were divided into two groups for cultured on normal and low oxygen tension until 10 passages. Cells were identified using flowcytometry for cd105 and cd34. At early and late passage, the expression of p21 and HIF-1a was examined using immunofluorescence while senescence was examined using Î²-galactosidase assay. Results: The results showed that in low oxygen cultures HIF-1a expression increased significantly (p <0.05) while p21 expression decreased significantly (p <0.05) as did the Î²-galactosidase assay. Conclusions: The conclusion of this research is low oxygen tension culture able to decrease premature senescence culture of invitro stem cells mesenchymal through obstacles p21 by HIF-1a. Keywords: p21 expression, HIF-1a expression, late passage, premature senescence.